2007
DOI: 10.1177/0363546507305018
|View full text |Cite
|
Sign up to set email alerts
|

15-Year Follow-up of Neuromuscular Function in Patients with Unilateral Nonreconstructed Anterior Cruciate Ligament Injury Initially Treated with Rehabilitation and Activity Modification

Abstract: 1Background: It has been suggested that neuromuscular function is of importance in the 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 43 publications
3
40
2
Order By: Relevance
“…However, the patients had poorer kinesthetic acuity than the uninjured controls. We have previously reported small differences between the injured and uninjured legs in the one-leg hop test and in knee muscle strength in this patient group, indicating good neuromuscular function (2). The results in the present study showing no differences, or even better values, in the one-leg hop test and knee muscle strength in the patients compared to the controls, further support our postulation of good neuromuscular function at the long-term follow-up in these patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the patients had poorer kinesthetic acuity than the uninjured controls. We have previously reported small differences between the injured and uninjured legs in the one-leg hop test and in knee muscle strength in this patient group, indicating good neuromuscular function (2). The results in the present study showing no differences, or even better values, in the one-leg hop test and knee muscle strength in the patients compared to the controls, further support our postulation of good neuromuscular function at the long-term follow-up in these patients.…”
Section: Discussionsupporting
confidence: 90%
“…They were all from a cohort of 100 consecutive patients with ACL injury at a non-professional, recreational or competitive, activity level, who had been followed prospectively and regularly for three years (4,8,36,37), and finally at 15 years after the initial injury (2,16).…”
Section: Patients and Controlsmentioning
confidence: 99%
“…Follow-up studies at 15 years after injury reported good functional and quadriceps/hamstring strength with ACL injuries treated with rehabilitation. However, many patients were required to modify their activity levels and avoidance of contact sport [87,88]. The KANON study (the Knee, Anterior cruciate ligament, NON-surgical versus surgical treatment) [89] found no difference in muscle power and functional tests between strength training with surgical intervention when compared to conservative management strategies at 2-5 years of followup.…”
Section: Decision Making Prior To Surgerymentioning
confidence: 99%
“…There are few long-term prospective studies (with a minimum of 10 years of follow-up) describing the natural history of the anterior cruciate ligament (ACL) de fi cient knee [ 3,47,87,108,[116][117][118] . It is important to de fi ne complete from partial ACL-de fi ciency and to realize that some studies combine patients with these diagnoses into one cohort, making conclusions dif fi cult on the effects of a completely de fi cient and nonfunctional ligament.…”
Section: Introductionmentioning
confidence: 99%